Genetic testing for the epilepsies: A systematic review. Issue 2 (10th December 2021) - Sheidley, Beth R.; Malinowski, Jennifer; Bergner, Amanda L.; Bier, Louise; Gloss, David S.; Mu, Weiyi; Mulhern, Maureen M.; Partack, Emily J.; Poduri, Annapurna
Abstract: Objective: Numerous genetic testing options for individuals with epilepsy have emerged over the past decade without clear guidelines regarding optimal testing strategies. We performed a systematic evidence review (SER) and conducted meta‐analyses of the diagnostic yield of genetic tests commonly utilized for patients with epilepsy. We also assessed nonyield outcomes (NYOs) such as changes in treatment and/or management, prognostic information, recurrence risk determination, and genetic counseling. Methods: We performed an SER, in accordance with PRISMA (Preferred Reporting Items for Systematic Reviews and Meta‐Analyses), using PubMed, Embase, CINAHL, and Cochrane Central through December of 2020. We included studies that utilized genome sequencing (GS), exome sequencing (ES), multigene panel (MGP), and/or genome‐wide comparative genomic hybridization/chromosomal microarray (CGH/CMA) in cohorts ( n  ≥ 10) ascertained for epilepsy. Quality assessment was undertaken using ROBINS‐I (Risk of Bias in Non‐Randomized Studies of Interventions). We estimated diagnostic yields and 95% confidence intervals with random effects meta‐analyses and narratively synthesized NYOs. Results: From 5985 nonduplicated articles published through 2020, 154 met inclusion criteria and were included in meta‐analyses of diagnostic yield; 43 of those were included in the NYO synthesis. The overall diagnostic yield across all test modalities was 17%, with the highest yield for GS (48%), followed by ES (24%), MGP (19%), and CGH/CMA (9%). The only phenotypic factors that were significantly associated with increased yield were (1) the presence of developmental and epileptic encephalopathy and/or (2) the presence of neurodevelopmental comorbidities. Studies reporting NYOs addressed clinical and personal utility of testing. Significance: This comprehensive SER, focused specifically on the literature regarding patients with epilepsy, provides a comparative assessment of the yield of clinically available tests, which will help shape clinician decision‐making and policy regarding insurance coverage for genetic testing. We highlight the need for prospective assessment of the clinical and personal utility of genetic testing for patients with epilepsy and for standardization in reporting patient characteristics.